(3QSGdI aj Gdabgs - (3eMeO Hf CMeO Hf GdeSfGhj Hf eMeO Hf CHj HcQ, CHh YHO Gddg GdOdGFj,J (B1136 (3g` s
(3ChdgG (B:s
(3HYO GdSdGe Ydi SGOJfG GdHOhQ hGdBLdI GdCYdGe s
(3BNQgG (B:s
(3hjbje HhLhOce CQcGf GdOjf hGdSdGe Ydjce hQMeJg hHQcGJg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B13 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B259s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdeGdcjs